Indoor wireless localization using twisted electromagnetic wave - Tay, Jui Hao (2017)
This report comprises a documentation of an indoor simulation of Orbital Angular Momentum (OAM) performance in signal transmitting by utilising a software program application known as MATLAB. Plane wave signal transmission is known globally and has been widely used for transmitting signals over a span of distances. Transmission performance have also greatly improved over the years, along with the limitations have been uncovered. However, plane wave transmission still has its flaws, as it can’t differentiate constructive and destructive signals which could pose as an interfering signal and weaken the real signal. In audio transmission, destructive signals could sum in noises decreasing the signal-to-noise ratio of the transmission or distort it. In localisation, destructive signals could greatly affect the azimuth and elevation results depending on the targeted frequency. The study on OAM signal transmission was purposed to prove that it could determine the phase of receiving signals with more than one antenna hence able to remove destructive signals. The simulation is an indoor controlled area, with 4 transmitting array sources comprising of 8 antennas each, and 1 receiver antenna array with 2 antennas at a known location. By performing the fingerprinting technique, with more sources will increase the confidences level of the results. This project could be furthered upon including reflection signals, gaussian noise test and outdoor environment test with different techniques like Angle or Arrival (AOA) or Time Difference of Arrival (TDOA).